Designing white water slalom courses for Olympic Games - Pollert jr. J.; Pollert sen. J.; Strogonov, V.; Švanda, O. (Copernicus GmbH, 2022)
The article provides an analysis of hydraulic technical requirements based on model investigations of the artificial slalom courses designed for the Tokyo 2020 Olympic Games. A main, "Competition Course" will be used for top level sporting events such as the Olympic Games, World Championships and/or World Cups, as well as commercial rafting and other recreational activities in Legacy. A second "Training Course" will be used for pre-race warmup, as well as for post-Games recreation and training opportunities for all varieties of whitewater enthusiasts, including youth development and instructional programs. The main aim of the physical model investigations was to evaluate these courses designs from a hydraulic point of view - to validate technical performance objectives and to determine the optimal positioning for hydraulic features within the channels, with respect to design criteria which are: optimal water depth at prescribed flows, optimal current velocities, optimal Games-ready hydraulic configurations, safety criteria compliance, suitability for various Legacy uses (per IOC intent).